Kearifan Lokal Kegiatan Usaha Tani Padi Ladang Oleh Suku Dayak di Kelurahan Budaya Pampang - Yulianto, Eko Harri; Mariyah, Mariyah; Anggraeni, Reny (AGRITEXTS: Journal of Agricultural Extension, 2025)
This study aims to determine local wisdom in rice farming activities in Pampang Cultural Village, North Samarinda Sub-district, Samarinda City. This research was conducted in Pampang Cultural Village, North Samarinda Sub-district, Samarinda City, from June to August 2022. Respondents were determined using the purposive sampling method by determining key informants, such as traditional heads and community leaders, totaling 10 people. This data collection is carried out by observation and interviews. The data were analyzed using descriptive analysis. The results of this study show that local wisdom in Pampang Cultural Village is still maintained, such as the celebration of harvest festival (Pelas Tahun), which is always held every year. However, there are some traditions that have been abandoned such as traditional activities before Nugal (Maraq Ngavan Ingaan) which were replaced by joint prayer events in their respective places of worship, transfer of land functions and the entry of the government's role in the development of rice farming through the formationof farmer groups fostered by Field Agricultural Extension Officers (PPL) under the auspices of the Agricultural Extension Center (BPP) and the Agriculture Office of Samarinda city.